Differences in cephalic and nasal indices between female and male students of the Faculty of Dentistry, University of Baiturrahmah, class of 2021: Perbedaan indeks sefalik dan indeks nasal antara perempuan dan laki-laki FKG Universitas Baiturrahmah angkatan 2021 - Khadijah Putri Nopan; Firdaus; Wulan Anggestia (Makassar Dental Journal PDGI Makassar, 2026)
Physical anthropology is the anthropometry of the skull and face, which studies the measurement of the dimensions of the skull and face. The cephalic in-dex is used in anthropometry to describe the shape of the human head. The nasal index is used in anthropology to help determine personal identity, parti-cularly differences in race, ethnicity, and gender. This study discusses the differences in cephalic and nasal indices between female and male students of the 2021 cohort at the Faculty of Dentistry, Baiturrahmah University. The population of this analytical observational study with a cross-sectional design con-sisted of 100 students of the 2021 class, obtained using purposive sampling. The data were analysed univariately and bivariately using the independent t-test and Spearman's rho using the SPSS v.25.0. The results showed that males had an average nasal index of 75.24%, while females had 71.64%, both classified as mesorrhine. The average cephalic index for males was 79.45%, and for females 76.73%, both also classified as mesocephalic, indicating a significant difference between the nasal index and cephalic index of male and female students (p<0.05). It was concluded that there was a significant dif-ference bet-ween the cephalic index and nasal index of male and female students.